Failure - Pond, Gina A., Rev. (Open Source Alexandrian, 2014)
In this podcast, Rev. Pond explores the practices of covens and witches and how certain aspects originally practiced at its inception might not be appropriate now if the dynamics of the group have change.
The Heretic Speaks episode 3, July 31, 2014
heretic-speaks_ep03_20140731.mp3 | MP3 Format Sound | 00:17:25 | 23.93 MB | 11/28/2018 10:34:16 AM | .mp3 |
Keywords: Pond, Gina, 1976-; Failure (Psychology); Podcasts